An assessment of genetic relationship in tea clones based on important chemical compound and yield potential - Bambang Sriyadi (Research Institute for Tea and Cinchona, 2015)
Assembling of new excellence high yielding and good quality tea clones was started from identification accession as gene sources, crossing design of parents, selection mother bushes and propagated vegetatively. Crossing beetwen two parent clones which near or remote genetic relationship in tea will failed. Assessment of genetic relationship clone accession was done using secondary datas from description of first and second tea clone generation which cultivated in Indonesia. Data of yield potentials and main chemical compound of quality among others catechine, gallat catechine, catechine gallo and cafeine were analysed using biplot and cluster analysis. The results showed that no correllation beetwen main chemical compound of quality and yield potentials. Biplot with two dimensions could be explained 92,5% variation of five characters and showed that yield has the highest and catechine the smallest variances. The first generation of tea clones was separated to second at the 46,79% similarity levels. At the 15,60% similarity levels, there were six clusters. GMB 1, GMB 2, GMB 6, GMB 9, and GMB 10 clones were in one cluster was caused of they had high of yield and catechine. GMB 4 and GMB 5 had similarity on medium yields, GMB 7 and GMB 11 had similarity on medium catechine and the highest yield, and GMB 3 and GMB 8 had similarity on low catechine. PS 1 with the lowest catechine gallo was separated to the others. The sixth cluster were SA 40, Kiara 8, SA 35, RB 3, and Cin 143 were characterized by low catechine and yields.